The environmental deposition of influenza virus from patients infected with influenza A(H1N1)pdm09: Implications for infection prevention and control. Issue 3 (May 2016) - Killingley, Benjamin; Greatorex, Jane; Digard, Paul; Wise, Helen; Garcia, Fayna; Varsani, Harsha; Cauchemez, Simon; Enstone, Joanne E.; Hayward, Andrew; Curran, Martin D.; Read, Robert C.; Lim, Wei S.; et al.
Summary: In a multi-center, prospective, observational study over two influenza seasons, we sought to quantify and correlate the amount of virus recovered from the nares of infected subjects with that recovered from their immediate environment in community and hospital settings. We recorded the symptoms of adults and children with A(H1N1)pdm09 infection, took nasal swabs, and sampled touched surfaces and room air. Forty-two infected subjects were followed up. The mean duration of virus shedding was 6.2 days by PCR (Polymerase Chain Reaction) and 4.2 days by culture. Surface swabs were collected from 39 settings; 16 (41%) subject locations were contaminated with virus. Overall, 33 of the 671 (4.9%) surface swabs were PCR positive for influenza, of which two (0.3%) yielded viable virus. On illness Day 3, subjects yielding positive surface samples had significantly higher nasal viral loads (geometric mean ratio 25.7; 95% CI 1.75, 376.0, p = 0.021) and a positive correlation ( r = 0.47, p = 0.006) was observed between subject nasal viral loads and viral loads recovered from the surfaces around them. Room air was sampled in the vicinity of 12 subjects, and PCR positive samples were obtained for five (42%) samples. Influenza virus shed by infected subjects did not detectably contaminate the vast majority of surfaces sampled. We question the relative importance of the indirect contact transmission of influenza via surfaces, though our data support the existence of super-spreaders via this route. The air sampling results add to the accumulating evidence that supports the potential for droplet nuclei (aerosol) transmission of influenza.